Principal Leadership Management in Building Student Character at State Elementary School 27 Palembang - Ardiansyah Saputra; Tri Widayatsih; Syaiful Eddy (Pusat Riset dan Inovasi Nasional, 2025)
Principal This study aims to analyze the principal's leadership management in building the character of students at SD Negeri 27 Palembang. Student character is an important aspect in education that not only focuses on academic achievement, but also the formation of a strong and ethical personality. The principal has a strategic role in managing resources, creating a conducive learning environment, and implementing character values in every aspect of learning. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation of the principal, teachers, and students. The results of the study indicate that the leadership of the principal at SD Negeri 27 Palembang contributes significantly to the formation of student character through habituation programs, extracurricular activities, and role models provided by educators. However, there are several obstacles such as lack of parental involvement and limited supporting facilities. In conclusion, effective principal leadership management plays an important role in building the character of students. A more optimal strategy is needed, including increasing communication with parents and strengthening school-based character education programs.